Changes in the cerebral phosphotransfer network impair energetic homeostasis in an aflatoxin B1-contaminated diet - Baldissera M.D. (2018)
© 2018, Springer Science+Business Media B.V., part of Springer Nature.The phosphotransfer network system, through the enzymes creatine kinase (CK), adenylate kinase (AK), and pyruvate kinase (PK), contributes to efficient intracellular energetic communication between cellular adenosine triphosphate (ATP) consumption and production in tissues with high energetic demand, such as cerebral tissue. Thus, the aim of this study was to evaluate whether aflatoxin B1 (AFB1) intoxication in diet negatively affects the cerebral phosphotransfer network related to impairment of cerebral ATP levels in silver catfish (Rhamdia quelen). Brain cytosolic CK activity decreased in animals fed with a diet contaminated with AFB1 on days 14 and 21 post-feeding, while mitochondrial CK activity increased, when compared to the control group (basal diet). Also, cerebral AK and PK activity decreased in animals fed with a diet contaminated with AFB1 on days 14 and 21 post-feeding, similarly to the results observed for cerebral ATP levels. Based on this evidence, inhibition of cerebral cytosolic CK activity is compensated by stimulation of mitochondrial CK activity in an attempt to prevent impairment of communication between sites of ATP generation and ATP utilization. The inhibition of cerebral AK and PK activity leads to impairment of cerebral energy homeostasis, decreasing the brain’s ATP availability. Moreover, the absence of a reciprocal compensatory mechanism between these enzymes contributes to cerebral energetic imbalance, which may contribute to disease pathophysiology.